Lea and Camila - Yee, Lisa; Hertz, Kellen (Girl of the year. Lea, 2016)
Lea's friend Camila visits from Brazil and together they make a mysterious discovery in an old mansion, but when Lea's best friend Abby hits it off with Camila, Lea feels left out and tries to reconnect with her friends and solve the mystery, too.